2022
DOI: 10.1038/s41467-022-28275-y
|View full text |Cite
|
Sign up to set email alerts
|

Mobilisation of deep crustal sulfide melts as a first order control on upper lithospheric metallogeny

Abstract: Magmatic arcs are terrestrial environments where lithospheric cycling and recycling of metals and volatiles is enhanced. However, the first-order mechanism permitting the episodic fluxing of these elements from the mantle through to the outer Earth’s spheres has been elusive. To address this knowledge gap, we focus on the textural and minero-chemical characteristics of metal-rich magmatic sulfides hosted in amphibole-olivine-pyroxene cumulates in the lowermost crust. We show that in cumulates that were subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 51 publications
(83 reference statements)
0
13
0
Order By: Relevance
“…This could be the (subordinate?) effect of additional processes that were not considered in the modeling, like gold recycling from Aurich sulfides in the lower crust (Shafiei et al, 2008;Richards, 2009;Holwell et al, 2022) or Au precipitation efficiencies higher than the range here simulated (Table S1). Figs.…”
Section: Cu and Au Endowments In Thin And Thick Arcs Modeled With Pro...mentioning
confidence: 86%
“…This could be the (subordinate?) effect of additional processes that were not considered in the modeling, like gold recycling from Aurich sulfides in the lower crust (Shafiei et al, 2008;Richards, 2009;Holwell et al, 2022) or Au precipitation efficiencies higher than the range here simulated (Table S1). Figs.…”
Section: Cu and Au Endowments In Thin And Thick Arcs Modeled With Pro...mentioning
confidence: 86%
“…We therefore conclude that while several models have explored the importance of sulphide melt resorption and chalcophile metal release back into an accompanying silicate melt (e.g. Kerr & Leitch, 2005;Reekie et al, 2019;Wieser et al, 2020, Chen et al, 2021Holwell et al, 2022), we currently do not have the necessary data to decipher any contributions from this process to the compositions of these unusual Tolbachik samples. Thus, we suggest that the simpler model for sulphide-undersaturated evolution across the entirety of the compositional range of the new monogenetic cone melts analysed in this study is the most likely explanation for the trends discussed here.…”
Section: Sulphide Immiscibility In the 1941 Eruption And At Cone 'Mt ...mentioning
confidence: 87%
“…9) Further targeted Se and Ag analysis of the primitive high-Mg and high-S melt inclusions from both sulphide-bearing and sulphide-free monogenetic cone eruptions would be key in unravelling any contributions from sulphide melt resorption and chalcophile metal release in the Tolbachik plumbing system (e.g. Holwell et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…If the sulfides form an interconnected network, for example, by wetting the grain boundaries of mantle olivine (Gaetani & Grove, 1999), they can substantially contribute to reducing the bulk electrical resistivity. Recent work has demonstrated that Cu–Au‐rich sulfide melt likely exists in cumulates near the base of the crust in regions with long‐lived magma generation, and investigated mechanisms for the mobilization and ascent of Cu–Au rich fluids upon reheating (Holwell et al., 2022). Metal preconcentration in fluids and/or magmas is thought to be a critical step in the formation of some mineral deposits and is closely related to the segregation of sulfide phases, which have been shown to persist at the base of the crust (Richards, 2011; Xu, Yang, et al., 2021; Zheng et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation for the events is one where ore‐forming fluids are generated from the lithospheric mantle that has been fertilized and metasomatized by fluids and melts derived from a much earlier geodynamic event, such as subduction (e.g., Groves, Santosh, & Zhang, 2020; Groves, Zhang, & Santosh, 2020). In such a scenario, former intensive and long‐lived arc magmatism may have left abundant sulfide‐bearing and metal‐rich cumulates near the base of the crust and a subsequent thermal anomaly, such as a mantle upwelling, triggered remelting, which provided abundant metals and S for post‐subduction fluid generation and mineral deposit formation (Richards, 2011; Hou et al., 2015; Xu, Hou, et al., 2021; see also Holwell et al., 2022) with a temporal gap suggesting independence of the fluid and mineral formation from the metamorphic and volcanic host rocks. This is consistent with studies that suggest the initial enrichment of metals in fluids and/or magmas is an important step in the formation of mineral deposits (Xu, Yang, et al., 2021; Zheng et al., 2019; see also Heinrich & Connolly, 2022).…”
Section: Discussionmentioning
confidence: 99%